Analisis Keterbacaan Instrumen Penilaian Psikomotorik pada Praktikum Biokimia Mahasiswa Pendidikan Biologi - Etika Dyah Puspitasari (Universitas Sebelas Maret, 2018)
This research aims to analyze the readability of the psychomotor assessment instrument by biochemistry assistant and to know the difficulty of using a psychomotor instrument that developed. This research is part of the research and development. Data were collected from fifteen biochemistry assistants in UAD's biology education program. The instruments used are questionnaires and interview guides. Data were analyzed by using quantitative and qualitative descriptive analysis techniques. The result of questionnaire analysis of psychomotor instability readiness by biochemistry assistant is 93,85% with high readability criterion. The linguistic aspect is 95,56% with a high criterion, the aspect of ease of use is 96,67% with a high criterion, instrument objectivity aspect 80% with high criterion and usefulness aspect in practice appraisal 100% with a high criterion. The difficulty in using psychomotor assessment instrument is caused by the division of student task in carrying out biochemistry experiment.